Optimasi Komposisi Menu Makanan bagi Penderita Tekanan Darah Tinggi Menggunakan Algoritme Genetika Adaptif - Raden Rafika Anugrahning Putri; Muhammad Tanzil Furqon; Randy Cahya Wihandika (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
High blood pressure or commonly called hypertension is a disease that can affect anyone. High blood pressure is one disease that can cause other diseases, such as heart attack and stroke. Blood pressure is high if systolic blood pressure is more than 140 mmHg and diastolic blood pressure is more than 90 mmHg. One thing that most affect the high blood pressure is an unhealthy diet. To set a healthy diet for people with high blood pressure then need to set the composition of foods with the needs of the body. A technique to get solution of foods for people with high blood pressure is by applying Adaptive Genetic Algorithm. Adaptive parameters are applied to the reproduction process mutation. The data used in the test is 146 Data of food ingredients classified into staple food, vegetable sources, sources of animal, vegetable and complementary. On this process of Adaptive Genetic Algorithm is used the permutation represented with integer with a length of chromosome 15 genes represented each digit of the number of food, methods of crossover with single-point crossover and mutation methods with reciprocal exchange mutation and elitism selection. As the results, the test performed obtained optimal parameters is the measure population of 200 individuals with an average fitness of 0,0774665, 90 generations with the average fitness of 0,0774665 and combinations cr = 0,8 and mr = 0,2 with the average fitness of 0,0780737.